Disaster Challenges for Persons with Disabilities: Risks, Barriers, and Inclusive Strategies - Lakshmi, A. Puvi (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
Persons with disabilities face various challenges globally in arrears to insufficient policies and moralities, restricted resources, approachability issues, deleterious perceptions, an absence of information and communication, deficient financial aid, and rejection from decisions that considerably impact their lives. In specific, disasters can make disabled people even more susceptible. It may be additional grim for them to abscond jeopardy during emergencies, and they run the menace of trailing indispensable assistive technology like spectacles, hearing assistance, mobility aids, and prescription drugs. People with disabilities experience an assortment of effects from catastrophes, counting an augmented mortality risk, damage, and property loss. They are frequently less expected to obtain initial cautions formerly a disaster, discovery means of evacuation and public shelters are dreadful to navigate and face a deficiency of sufficient care and shelter choices, as well as being unnoticed in relief and recovery efforts. Beside with statistics on the figures of disabled people exterminated and incapacitated during calamities around the world, this study demonstrates the various problems stumble upon by people with disabilities through disaster situations. This chapter is based on reviewing the reports and studies endorsed in disability and disaster in a descriptive nature. It describes the difficulties confronted by various disability communities during and after diverse catastrophes across the world. It also looks at several policy initiatives preordained to address these glitches on a global scale.